Assessment of the haematological profile after appendectomy using linear titanium stapler clips: an experimental study in rats - Bajrić, Amela; Katica, Muhamed; Katica, Aida; Smajović, Alisa; Sivić, Mujo; Rukavina, Dunja; Čelebić, Mirza; Zahirović, Amir; Bajrić, Ajla; Delibegović, Samir (Scripta Medica, 2021)
Introduction: The technique of closing the appendiceal stump using linear titanium stapler clips is being used more and more frequently in laparoscopic surgery, despite the good practice in the use of resorbable single endoloop vicryl ligatures and/or the non-resorbable plastic hem-o-lok clips. No light has been shed on potential undesirable effects on the haemathological profile of the use of titanium stapler clips. This experimental study aimed at establishing any possible undesirable effect of linear titanium stapler clips and single resorbable vicryl endoloop ligatures on the blood cells in rats following appendectomy. Methods: A total of 70 adult rats were used, divided into a control group (n = 10), and two experimental groups (n = 30 + 30). The appendices were removed from the rats in the first experimental group using titanium stapler clips and in the second experimental group the appendiceal stump using resorbable endoloop vicryl ligatures was closed. In both experimental groups three sub-groups with ten animals each were formed, from which peripheral blood from a tail vein on days 7, 28 and 60 was removed postoperatively, in order to assess the usual haematological parameters. Stained blood smears were also analysed in order to establish any poikilocytotic erythrocytes present. Results: In the first experimental group, with the titanium stapler clips, more than 25 % neutrophils were found on day 7, which is a significantly different result (p < 0.05) to the control group. In the second experimental group, there were more neutrophils than in the titanium stapler clips group, especially on days 7 and 60 and the results of these two sub-groups differ statistically significantly, p < 0.05. Hypochromia was found in the endoloop vicryl ligatures group, as well as in the titanium stapler clips sub-group on day 28, due to lower haemoglobin values which were significantly different to the control group, p < 0.05. Moderate levels of annulocytes, spherocytes and stomatocytes were found in most experimental groups. Conclusion: The results of this study favour the use of linear titanium stapler clips over resorbable single endoloop vicryl ligatures, because a less unfavourable effect was established on the blood cells of the experimental rats with their use.